Keep Your Friends Close, but Your Enemies Closer: Role of Acid Sphingomyelinase During Infection and Host Response - Chung, Ha-Yeun; Claus, Ralf A. (Frontiers in Medicine, 2021)
Breakdown of the inert and constitutive membrane building block sphingomyelin to the highly active lipid mediator ceramide by extracellularly active acid sphingomyelinase is tightly regulated during stress response and opens the gate for invading pathogens, triggering the immune response, development of remote organ failure, and tissue repair following severe infection. How does one enzyme and one mediator manage all of these affairs? Under physiological conditions, the enzyme is located in the lysosomes and takes part in the noiseless metabolism of sphingolipids, but following stress the protein is secreted into circulation. When secreted, acid sphingomyelinase (ASM) is able to hydrolyze sphingomyelin present at the outer leaflet of membranes to ceramide. Its generation troubles the biophysical context of cellular membranes resulting in functional assembly and reorganization of proteins and receptors, also embedded in highly conserved response mechanisms. As a consequence of cellular signaling, not only induction of cell death but also proliferation, differentiation, and fibrogenesis are affected. Here, we discuss the current state of the art on both the impact and function of the enzyme during host response and damage control. Also, the potential role of lysosomotropic agents as functional inhibitors of this upstream alarming cascade is highlighted.